2020
DOI: 10.3171/2020.3.focus2043
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing pre-, intra-, and postoperative management of patients with sellar pathology undergoing transsphenoidal surgery

Abstract: OBJECTIVEPerioperative management of patients with sellar lesions is complex, requiring input from a multidisciplinary team of specialists for ongoing management of both endocrinological and neurosurgical issues. Here, the authors reviewed the experience of a single multidisciplinary center over 10 years to identify key postoperative practices that ensure positive outcomes for patients with sellar lesions who undergo transsphenoidal surgery. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…These patients should be treated as soon as possible to avoid deterioration and several reports regarding treatment of delayed hyponatremia to prevent severe symptoms have been presented [25,[40][41][42], with the latter by Deaver et al noting that mild fluid restriction (up to 1.5 liters daily) was an effective approach for preventing readmission for hyponatremia after TSS for a pituitary adenoma. Based on the report by D. J. Cote [43], restrictions of fluid (to 1.0 liters daily) and oral salt intake (3-6 g/day) were used for patients in the present cohort with delayed hyponatremia to improve symptoms. Finally, though treatment with the oral vasopressin receptor antagonist tolvaptan can be useful for cases with SIADH [9], that drug was not available in Japan until 2020.…”
Section: Discussionmentioning
confidence: 99%
“…These patients should be treated as soon as possible to avoid deterioration and several reports regarding treatment of delayed hyponatremia to prevent severe symptoms have been presented [25,[40][41][42], with the latter by Deaver et al noting that mild fluid restriction (up to 1.5 liters daily) was an effective approach for preventing readmission for hyponatremia after TSS for a pituitary adenoma. Based on the report by D. J. Cote [43], restrictions of fluid (to 1.0 liters daily) and oral salt intake (3-6 g/day) were used for patients in the present cohort with delayed hyponatremia to improve symptoms. Finally, though treatment with the oral vasopressin receptor antagonist tolvaptan can be useful for cases with SIADH [9], that drug was not available in Japan until 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Since the declaration of the opioid epidemic as a United States public health emergency in 2017, recent research has identified alternatives to opioid use in the perioperative period 36 . Nonsteroidal anti‐inflammatory drugs and anticonvulsants have been shown to reduce postoperative opioid use 6,37 . A randomized controlled trial demonstrated that scheduled postoperative intravenous ibuprofen in patients undergoing EESBS decreased pain scores and opioid use, with no increased risk of hemorrhagic complications compared with placebo 6 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Nonsteroidal anti-inflammatory drugs and anticonvulsants have been shown to reduce postoperative opioid use. 6,37 A randomized controlled trial demonstrated that scheduled postoperative intravenous ibuprofen in patients undergoing EESBS decreased pain scores and opioid use, with no increased risk of hemorrhagic complications compared with placebo. 6 Anticonvulsants such as pregabalin have been shown to reduce postoperative pain scores and inpatient and outpatient opioid use compared with placebo in patients who underwent elective craniotomies.…”
Section: Postoperative Optimization: Alternatives To Opioid Usementioning
confidence: 99%
“…The use of glucocorticoids is the most important in the perioperative period of patients with craniopharyngioma. Patients after surgery undergo assessments serum cortisol daily morning (102). At most centers, all patients are given stress doses of hydrocortisone (100 mg IV) or other glucocorticoid at the time of surgery, and this dose is tapered quickly over 2-3 days for a total of about five doses (106)(107)(108).…”
Section: Management Perioperative Managementmentioning
confidence: 99%
“…Acute disorders of water metabolism can manifest in a triphasic pattern (in ~3% of patients): an initial polyuric phase, a subsequent antidiuretic phase (the patients can temporarily concentrate urine and syndrome of inappropriate ADH secretion (SIADH) and hyponatremia develops), and a final polyuric phase that is usually chronic ( 101 ). To screen for potential development of postoperative DI and SIADH, patients after surgery undergo assessments of serum sodium and urine-specific gravity every 6 h ( 102 ).…”
Section: Managementmentioning
confidence: 99%